Mucin gene expression in Barrett's oesophagus: an in situ hybridisation and immunohistochemical study. Issue 6 (1st December 2000) - Arul, G S; Moorghen, M; Myerscough, N; Alderson, D A; Spicer, R D; Corfield, A P
Abstract : BACKGROUND AND AIMS: Mucin genes are expressed in a site specific manner throughout the gastrointestinal tract. Little is known about the expression pattern in the oesophagus. In this study we have investigated MUC gene expression in both the normal oesophagus and specialised intestinal metaplasia (Barrett's oesophagus). PATIENTS: Archived paraffin embedded material from eight specimens of normal oesophagus, 18 Barrett's oesophagus, eight gastric metaplasia, six high grade dysplasia, and six cases of adenocarcinoma were examined for expression of the mucin genes MUC1–6. METHODS: Mucin mRNA was detected by in situ hybridisation using [ 35 S] dATP labelled oligonucleotide probes. Mucin core protein was detected by immunohistochemistry. RESULTS: Normal oesophagus expressed MUC5B in the submucosal glands and MUC1 and MUC4 in the stratified squamous epithelium. Barrett's oesophagus strongly expressed MUC5AC and MUC3 in the superficial columnar epithelium, MUC2 in the goblet cells, and MUC6 in the glands. In high grade dysplasia and adenocarcinoma there was downregulation of MUC2, MUC3, MUC5AC, and MUC6, but upregulation of MUC1 and MUC4 in half of the specimens examined. CONCLUSIONS: Normal oesophagus and Barrett's oesophagus have a novel pattern of mucin gene expression. Barrett's oesophagus expressed the mucins associated with normal gastric epithelium and normal intestinal epithelium. While most mucin genes were downregulated in severely dysplastic and neoplastic tissues, there was upregulation of the membrane bound mucins MUC1 and MUC4. This may prove useful in detecting early signs of progression to adenocarcinoma of the oesophagus.